The littérature mineure of François Bon - Helena Chadderton (Studies in 20th & 21st Century Literature, 2017)
This article shows how the work of contemporary author François Bon can be read as an example of Deleuze and Guattari’s littérature mineure. Bon’s work stands out on the French literary scene for its capacity to be political in both its content and its use of form. Furthermore, Bon brings form and content together by demonstrating the impact of language and textual features on the perception of social division. Focussing on characteristic features of Bon’s style pertaining to genre, syntax and rhythm, I propose that the relationship between reality and text in Bon’s work is one of mutual effect and influence rather than one of a simple transferral of meaning from one to the other, recalling the definition of Deleuze and Guattari’s agencement. In the socially marginal contexts Bon represents the reader is encouraged to focus on the political potential of the text and notice the ways in which major use of language entrenches marginality.
Keywords: François Bon; littérature mineure; marginality; social division; style